Recent Advances in the Metabolic Engineering of Yeasts for Ginsenoside Biosynthesis - Chu, Luan Luong; Montecillo, Jake Adolf V.; Bae, Hanhong (Frontiers in Bioengineering and Biotechnology, 2020)
Ginsenosides are a group of glycosylated triterpenes isolated from Panax species. Ginsenosides are promising candidates for the prevention and treatment of cancer as well as food additives. However, owing to a lack of efficient approaches for ginsenoside production from plants and chemical synthesis, ginsenosides may not yet have reached their full potential as medicinal resources. In recent years, an alternative approach for ginsenoside production has been developed using the model yeast Saccharomyces cerevisiae and non-conventional yeasts such as Yarrowia lipolytica and Pichia pastoris. In this review, various metabolic engineering strategies, including heterologous gene expression, balancing, and increasing metabolic flux, and enzyme engineering, have been described as recent advanced engineering techniques for improving ginsenoside production. Furthermore, the usefulness of a systems approach and fermentation strategy has been presented. Finally, the present challenges and future research direction for industrial cell factories have been discussed.